Global trends and inequalities in the burden of drug use disorders: a comprehensive analysis from 1990 to 2021 with future projections - Zhou, Jian; He, Menglin; Zhou, Guojun; Yang, Taoran; Wang, Rurong; Li, Xuehan (Frontiers in Public Health, 2025)
BackgroundDrug use disorders (DUDs) pose a major global health challenge, with limited comprehensive data across demographic and socioeconomic groups.MethodsUsing data from the Global Burden of Disease (GBD) 2021, we analyzed disability-adjusted life years (DALYs), deaths, prevalence, and incidence of DUDs from 1990 to 2021, stratified by sex, age, country, and Socio-Demographic Index (SDI). Trends were assessed using Joinpoint regression analysis, while cross-inequalities were evaluated through the Slope Index of Inequality (SII) and Concentration Index (CI). Nordpred projected future burden.ResultsFrom 1990 to 2021, DALYs increased by 14.7%. Males and individuals aged 25–29 experienced the highest burden. High-SDI countries recorded the greatest DALYs and deaths. The SII increased from 82.4 in 1990 to 289.24 in 2021, and the CI revealed a disproportionate concentration of DUDs burden in high-SDI countries. Projections suggest that by 2044, DALYs will rise by 12.9 million, mainly due to opioid use disorders.ConclusionThe global burden of DUDs has increased significantly with widening health inequalities across SDI levels. Targeted interventions, particularly addressing the opioid crisis, are essential to manage and mitigate future impacts.